''Rogues Gallery'' and India politics - "Sahni, J. N." (New Delhi, 1982)
This book covers the period from 1965 to 1981. it comprises the instant reactions of the author towards political developments in the country during the most controversial and spectacularly transitional period in the nation's life since Independence. The period furthermore constitutes a turning point in the relationship of the Centre and the states, of the majorities and the minorities. In this book author comments o men and matters with an authority that he draws from his rich background of personal experience in the political field during and since national struggle.
Keywords: India politics and government